IS ARTIFICIAL INTELLIGENCE GOOD FOR HUMANITY? (Moment Magazine)
The article discusses views of Jewish experts including Nick Bostrom, a Swedish philosopher; Miriam Vogel, president of of EqualAI; and David Zvi Kalman, a multimedia artist, on the impact of artificial intelligence. Topics discussed include their views on whether AI is good for humanity?; what Judaism can teach us about AI; and the complexity of AI. It also mentioned the definition and terminology of AI.